Еpidermolytic palmoplantar keratoderma of Vörner. Case report. - Miteva, L.; Botev, I. (European Journal of Pediatric Dermatology, 2008)
The Authors describe a case of palmoplantar keratoderma in a 2-year-old boy, arisen 14 weeks after birth according to the parents. The clinical picture, histopathologic findings and careful analysis of the literature enabled us to define this form of palmoplantar keratosis as epidermolytic palmoplantar keratoderma of Vörner. The typical clinical presentation, the differential diagnosis and the classification of hereditary palmoplantar keratoses are discussed.